Evaluation of safety and efficacy of Tirofiban injection for treating acute ischemic stroke beyond standard time window - Qian Yang; Qiaofeng He; Xinfa Mao; Weibing Fan; Xin Luo (Scientific Reports)
Abstract To evaluate the safety and efficacy of tirofiban in the treatment of acute ischemic stroke (AIS). Clinical data of 152 AIS patients with small vessel occlusion admitted in 2023 were retrospectively analyzed. These patients did not receive intravenous thrombolysis and endovascular treatment within 72 h of onset. Patients were divided into two groups (n = 76 each group): a dual antiplatelet group (aspirin + clopidogrel for 14 days, followed by aspirin alone) and a tirofiban group (dual antiplatelet therapy plus tirofiban). Neurological deficits and functional outcomes were assessed before treatment, on day 7, and day 90. Serum hs-CRP and IL-6 levels were measured prior to treatment and on day 7. Symptom aggravation, symptomatic bleeding, and mortality within 90 days were also recorded. Baseline characteristics of the two groups were comparable. Tirofiban treatment significantly improved mRS scores from baseline to day 7 (t = 5.94, p < 0.001) and day 90 (t = 5.67, p < 0.001) (F = 53.13, p < 0.001), with improvements persisting after adjusting for baseline scores (F = 32.56, p < 0.001). Moreover, tirofiban treatment significantly reduced NIHSS scores at days 7 (mean difference = − 0.97 (95% CI: − 1.53, − 0.41); t = 3.57, p < 0.001) and 90 (mean difference = − 0.82 (95% CI: − 1.29, − 0.34); t = 3.97, p < 0.001) and increased Barthel Index scores at days 7 (mean difference = 9.8 (95% CI: 4.3, 15.3); t = − 3.14, p = 0.002) and 90 (mean difference = 11.7 (95% CI: 6.2, 17.2); t = − 4.41, p < 0.001), indicating greater functional independence. No significant differences were observed between the two groups in inflammatory markers (hs-CRP and IL-6), intracranial hemorrhage, or mortality. However, there was a trend toward a higher rate of deterioration in the dual antiplatelet group (13.4% vs. 5.6%). Tirofiban combined with conventional treatment significantly improves neurological deficits and disease outcomes in AIS patients without increasing the risk of bleeding and mortality.